THE EFFECTS OF TEACHING METHOD AND EMOTIONAL INTELLIGENCE UPON STUDENT’S SPEAKING SKILL - Supadi Supadi (Deiksis, 2014)
The objective of this research is to investigate student?s speaking skill at the private vocational school in east Jakarta, for investigating: 1) there is effect of teaching method upon student?s speaking skill, 2) there is effect emotional intelligence upon student?s speaking skill, 3) there is interaction between teaching method and emotional intelligence upon student?s speaking skill. Method used in this research in experimental method. The population is all students and the sample of 40 students who obtained a random sampling technique that use cluster sampling. Instrument that is used is result test of student?s speaking skill with 35 items that is tested validity with reliability coefisient = 0,82, questionnaire 38 items of emotional intelligence that is tested validity with reliability coefficient = 0, 72. Data analysis uses analysis of variance two-ways. Rearch result shows that there sre effects of teaching method and emotional intelligence upon student?s speaking skill. For increasing student?s speaking skill it is needed enhance of teaching method and emotional intelligence.Keywords: Teaching, method, emotional, intelligence, speakingPENGARUH